2020
DOI: 10.1007/s10460-020-10160-3
|View full text |Cite
|
Sign up to set email alerts
|

Using smartphone app collected data to explore the link between mechanization and intra-household allocation of time in Zambia

Abstract: Digital tools may help to study socioeconomic aspects of agricultural development that are difficult to measure such as the effects of new policies and technologies on the intra-household allocation of time. As farm technologies target different crops and tasks, they can affect the time-use of men, women, boys, and girls differently. Development strategies that overlook such effects can have negative consequences for vulnerable household members. In this paper, the time-use patterns associated with different l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…6 Future studies may also use compositional regression approaches to better capture the inherent trade-offs between different time-use activities, which may affect the outcome variable "farm share time". However, insights from a prior study using the same timeuse data and compositional data (Daum et al, 2021) suggest that this does not undermine the findings. Daum et al (2021) also find that the "farm share time" during land preparation and weeding are significantly correleated with the degree of mechanization and gender and that "farm share time" during harvesting is significantly correlated with gender.…”
Section: F B G M F B G M F B G Land Preparation Periodmentioning
confidence: 80%
See 1 more Smart Citation
“…6 Future studies may also use compositional regression approaches to better capture the inherent trade-offs between different time-use activities, which may affect the outcome variable "farm share time". However, insights from a prior study using the same timeuse data and compositional data (Daum et al, 2021) suggest that this does not undermine the findings. Daum et al (2021) also find that the "farm share time" during land preparation and weeding are significantly correleated with the degree of mechanization and gender and that "farm share time" during harvesting is significantly correlated with gender.…”
Section: F B G M F B G M F B G Land Preparation Periodmentioning
confidence: 80%
“…However, insights from a prior study using the same timeuse data and compositional data (Daum et al, 2021) suggest that this does not undermine the findings. Daum et al (2021) also find that the "farm share time" during land preparation and weeding are significantly correleated with the degree of mechanization and gender and that "farm share time" during harvesting is significantly correlated with gender. Another limitation is that the study provides only limited insights into the adequacy of calorie intake for individuals in different household categories (manual, animal, and tractor).…”
Section: F B G M F B G M F B G Land Preparation Periodmentioning
confidence: 80%
“…In a study in Nigeria, tractor use raised real incomes by 13% (Takeshima and Lawal 2020). Rising agricultural labor productivity often enables households to allocate time away from agriculture and pursue off-farm work (Daum et al 2021a;Kansanga et al 2020;Ma et al 2018;Theis et al 2019). Pingali (2007) argues that "poor households benefit the most since the released labor can be reallocated for other income-earning activities or leisure" (p. 2800).…”
Section: Income Effects and Economic Spilloversmentioning
confidence: 99%
“…Mechanization may be of particular relevance to reducing child labor in agriculture (Takeshima and Vos 2022). Seventy percent of child labor is in agriculture, affecting the present and future livelihoods of 112 million children (ILO 2021), by negatively affecting their well-being and health as well as the ability to play or go to school (Daum et al 2021a;ILO 2021). Mechanization may also affect mental health as it can be associated with higher social status (Daum et al 2021a) and increased resilience, as shown above.…”
Section: Well-being and Healthmentioning
confidence: 99%
“…In the current neoliberal development paradigm, critics argue that development theory and practice should (re-)connect with feminist theories of care, justice, and emancipation to achieve substantive and sustainable social change (Cornwall and Rivas 2015;Nyambura 2015;Wallace 2020). In contemporary African agricultural restructuring and transition, known as the New Green Revolution for Africa (GR4A), scholars highlight and challenge the gendered, unequal outcomes of interventions for, among others, agricultural mechanization (Daum et al 2021;Kansanga et al 2019), new and improved seeds and varieties (Addison and Schnurr 2016;Bergman Lodin 2012), new breeds (Wangui 2008), irrigated agriculture (Nation 2010), inorganic fertilizer and pesticide use (Christie et al 2015;Luna 2020), market integration (Quisumbing et al 2015;Tavenner and Crane 2018) and commercialization (Gengenbach 2020). Recent studies of national agriculture policy in Africa consider its limitations with regard to advancing equality.…”
Section: Introductionmentioning
confidence: 99%